Comprehensive Characterization of Bihormonal Cells and Endocrine Cell Lineages in Mammalian Pancreatic Islets - Xin‐Xin Yu; Peng Peng; Yi‐Ning Wang; Mao‐Yang He; Shuang He; Chen‐Tao Jin; Liu Yang; Xi Wang; Jia‐Xi Zheng; Jie Gao; Cheng‐Ran Xu (Advanced Science)
Abstract Understanding the role and prevalence of bihormonal cells in pancreatic islets and their potential in β‐cell restoration is critical but remains ambiguous. Using genetically engineered mouse strains with specific fluorescent markers and advanced imaging flow cytometry, it is found that bihormonal cells are exceedingly rare. Single‐cell RNA sequencing reveals that Gcg+Ppy+ and Gcg+Ins+ bihormonal cells closely resemble α‐cells or PP‐cells and α‐cells, respectively, indicating they are neither unique lineages nor transitional states. Dual‐recombinase lineage tracing further demonstrates that embryonic Gcg+Ins+ cells resolve into monohormonal α‐cells. Applying these insights, the scarcity of bihormonal cells in diabetic mouse models is confirmed, suggesting a limited role in β‐cell regeneration. By excluding bihormonal influences, endocrine cell classification is redefined in mouse and human islets through gene coexpression network analysis, identifying distinct subtypes and regulatory modules while uncovering species‐specific differences. Additionally, two unique δ‐cell subpopulations are identified in human islets. Collectively, this study provides a comprehensive characterization of bihormonal cells, refines endocrine cell taxonomy, and underscores the translational challenges in modeling human islet biology in mice.